An application profile for research collaboration and information management. Issue 3 (6th July 2015) - Nonthakarn, Chariya; Wuwongse, Vilas
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to design an application profile that will enable interoperability among research management systems, support research collaboration, and facilitate the management of research information. Design/methodology/approach – The approach is based on the Singapore Framework for Dublin Core Application Profile, a framework for designing metadata schemas for maximum interoperability. The application profile is built from gathering stakeholders' requirements in research community and integrates four types of research information, i.e., information on researchers, research projects, research outputs, and research reports, which benefits researchers, research managers, and funding agencies. Findings – The resultant application profile is evaluated against widely used similar metadata schemas and requirements; and is found to be more comprehensive than the existing schemas and meets the collected requirements. Furthermore, the application profile is deployed with a prototype of research management system and is found works appropriately. Practical implications – The designed application profile has implications for further development of research management systems that would lead to the enhancement of research collaboration and the efficiency of research information management. Originality/value – The proposed application profile covers information entire the research development lifecycle. Both schema and information can be represented in Resource Description Framework format for reusing purpose and linking with other information. This enables users to share research information, co-operate with others, funding agencies and the community at large, thereby allowing a research management system to increase collaboration and the efficiency of research management. Furthermore, researchers and research information can be linked by means of Linked Open Data technology.